Numerical Analysis of Deep Rc Beam With Circular Holes Thin Shear Plates - Ho, Hong Yeu (2021)
Reinforced concrete (RC) deep beam in massive structures are constructed to provide sufficient load carrying capacity. However, concrete honeycomb due to reinforcement congestion is a common problem in RC deep beam. Circular holes thin shear plates appear to be an effective substitute to conventional shear links, providing higher load carrying capacity yet using less space. Finite element analysis (FEA) using ABAQUS software is capable of solving complex deep beam problems in a timely and cost-effective manner. In this study, a numerical model was established to yield good matching results to the experimental results published by Jasim, et al. (2020). The verified numerical model was used to further study the test specimens with 50 mm, 75 mm, 100 mm, 125 mm, and 150 mm circular holes spacing. Load-displacement curves were plotted to evaluate the load-carrying capacity of the test specimens. A maximum 2.90 % improvement was observed in the test specimen with 100 mm circular holes spacing, N100. Therefore, N100 was determined as the optimum design for the further discussion of stress distribution and crack pattern. Von Mises stress contour of the concrete and reinforcement were generated to investigate the stress distribution over the loading process. Reinforcement stress capacity of N100 is increased by 1.79 %, but concrete stress capacity is reduced by 2.23 %. Plastic strain magnitude (PEMAG) diagram and concrete tension damage contour provide a clear visualization of the crack pattern. Shear compression failure is deduced based on the diagonal cracks accumulating at the concrete strut.